Extração da pectina do maracujá-amarelo (Passiflora edulis f. flavicarpa) - Nascimento, Francieli Aparecida do (2014)
Due to the large growth of the juice pulp of the yellow passion fruit (Passiflora edulis f. Flavicarpa) industries, the focus of this study was to investigate some alternatives to the problems of waste generation. Today, the industry generate a large volume of waste of the passion fruit shells that are used only in animal feed but, it could be used as raw material to pectin extraction which has a high added-value. Thus, the yellow passion fruit shells were used as raw material to pectin extraction. Normally pectins are extracted with acidified water with phosphoric, acetic, sulfuric, nitric or chloridric acid. The extraction with these acids presents several drawbacks such as water pollution and corrosion. Strong acid solutions can cause partial hydrolysis of the pectin chains, releasing molecules that cannot be precipitated by alcohol addition and then decreasing the extraction yield. Therefore, it is observed the necessity of additional studies to identify the ideal conditions to pectin extract by organic acids such as citric acid, to obtain a product with high esterification degree, thereby favoring the food industry economic and environmentally. The aim of this work was to compare the yield and quality of the esterification degree of the pectin extracted with citric acid in different conditions of time, pH, reaction temperature and agitation. For the esterification reaction, the best result of the experiments was 63.80% yield in the pH = 2.0 at 95 °C in 50 minutes of extraction with the agitation condition.